2010
DOI: 10.1097/gim.0b013e3181e38fb6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of population screening for fragile X syndrome

Abstract: Purpose: To conduct a systematic review of literature regarding population-based screening for fragile X syndrome in newborns and women of reproductive age, either before or during pregnancy. Methods: Seven electronic databases were searched for English language studies published between January 1991 and November 2009. Data extraction was performed for all included studies. Results were synthesized using a narrative approach. Results: One article that examined offering newborn screening for fragile X syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 85 publications
2
91
1
Order By: Relevance
“…25 There is much discussion about possible expansion and evaluation of NBS programs to include other conditions such as DMD [25][26][27] and FXS. [28][29][30] Similarly, SMA could be considered for inclusion. 7 When presented with screening options, such as screening children in the newborn or infant period, participants in our study highlighted the complexity of choosing an appropriate time to test, because of the variability in the phenotype between SMA types and even within the same SMA type.…”
Section: Description Of Participantsmentioning
confidence: 99%
“…25 There is much discussion about possible expansion and evaluation of NBS programs to include other conditions such as DMD [25][26][27] and FXS. [28][29][30] Similarly, SMA could be considered for inclusion. 7 When presented with screening options, such as screening children in the newborn or infant period, participants in our study highlighted the complexity of choosing an appropriate time to test, because of the variability in the phenotype between SMA types and even within the same SMA type.…”
Section: Description Of Participantsmentioning
confidence: 99%
“…7 The psychosocial consequences of preconceptional CGG repeat length screening have been studied in great detail and were found to be in favor of a generalized screening. [8][9][10] In addition, the attitudes of key medical care stakeholders toward the challenges of general population-based screening programs were found to be favorable, 6,11 and preconceptional testing was most endorsed. 12 Despite these well-studied advantages of a population-based screening and the wide acceptance among key stakeholders of medical care, screening programs have so far only been conducted in research settings.…”
Section: Introductionmentioning
confidence: 99%
“…Although funding for genetic carrier screening varies internationally, for tests in which the consumer bears the cost of the screening, genetic counseling resources should be factored into the screening fee so that genetic counseling support is accessible to those considering and undergoing screening as well as those who receive carrier results. While much research has shown that FXS carrier screening is feasible (Hill et al 2010), limited awareness of FXS and of the availability and implications of genetic screening was identified as a major issue which may impact the utilization of a screening program. This concern is not unique to FXS and is a potential barrier to the delivery of genetic carrier screening services.…”
Section: Discussionmentioning
confidence: 99%
“…As such, FXS carrier screening, either stand-alone or as part of expanded screening, provides a useful model through which to consider carrier screening approaches because of the complexity and duality of risk information provided (Henneman et al 2016). As outlined by Hill et al (2010), arguments for carrier screening for FXS include a high prevalence (which may be up to 1 in 2500 in males and females (Hagerman 2008)) and high carrier frequency (recently reported to be 1 in 179 estimated for North American populations (Hantash et al 2011)), the prevalence of premutation alleles estimated as 1:209 in females and 1:430 in males (Tassone et al 2012), and an accurate testing method amenable to screening populations (Tassone et al 2008) which identifies an expanded CGG repeat in the FMR1 gene (the cause of FXS in over 99 % of cases). In addition, the condition is well understood and defined; there are a range of significant phenotypic effects associated with the full mutation (FM ≥200 hypermethylated CGG repeats) including intellectual disability and cognitive, behavioral, and medical problems, which have a substantial impact on the affected individual and their family (Hagerman and Hagerman 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation